Biochemical profiling of tuberculosis patients and the impact of co-infection and comorbidities - Irum Javid; Muhammad Riaz; Fatima Yousaf; Shamim Khan; Salma Shahid; Farrukh Bashir; Ghulam Rasool (European Journal of Inflammation)
Backgrounds: Tuberculosis (TB) is a contagious disease caused by Mycobacterium tuberculosis that primarily affects the lungs but can also affect other organs of the body. In 2022, World Health Organization (WHO) reported that 202 countries account for more than 99% of TB cases around the world. Pakistan ranks 5 th among the countries with the highest burden of tuberculosis. The current study was planned to evaluate the biochemical profile of TB patients coinfected with other infectious and metabolic disorders. Methods: A total of 366 Ziehl Neelsen (ZN) stain positive TB patients were included in the study, along with positive controls who had comorbidities such as diabetes (62), hepatitis C virus (HCV) (46), human immunodeficiency virus (HIV) infection (11), and myocardial infarction (MI) (9). Biochemical parameters were determined photometrically by kit methods. Results: Among the 366 cases, 52% were females and 48% were males, with a mean age of 44 ± 5.803 years. Out of the ZN positive TB patients, 258 were found TB positive through PCR. Among the PCR positive TB patients, these patients were coinfected with diabetes (24%), HCV (17.8%), HIV (4.2%), and myocardial infarction (3.4%). Significant (P < 0.0001) variation in biochemical indices were observed in TB patients alone and those coinfected with diabetes, hepatitis C virus (HCV), and human immunodeficiency virus (HIV). Patients with co-morbidities of TB + Diabetes + HCV showed an increase in the levels of blood glucose, serum urea, creatinine, bilirubin, ALT, AST, ALP, IgG, IgM, potassium, and phosphorous. The group with co-morbidities of tuberculosis, hepatitis C, and HIV showed increases in the levels of ALP, IgG, and IgM. Conclusion: The study concluded that variations in biochemical indices observed in studied population provide useful information for the diagnosis of comorbidities of TB patients with metabolic and infectious diseases.